Identifying Potent, Selective Protein Tyrosine Phosphatase Inhibitors from a Library of Au(I) Complexes - Karver, Mark R. (2009)
Therapeutic inhibition of protein tyrosine phosphatase activity is a compelling yet challenging approach to the treatment of human disease. Towards this end, a library of 40 gold complexes with the general formula R(3)P–Au–Cl was screened to identify novel inhibitors of PTP activity. The most promising inhibitor obtained for the lymphoid tyrosine phosphatase LYP, (2-pyridine)(Ph(2))P–Au–Cl, is one of the most potent and selective LYP inhibitors identified to date with an IC(50) of 1.5 ± 0.3 µM, 10-fold selectivity for LYP over PTP-PEST, HePTP and CD45 in vitro and activity in cellular studies as well.